2023
DOI: 10.1038/s41416-023-02466-w
|View full text |Cite
|
Sign up to set email alerts
|

Supporting gut health with medicinal cannabis in people with advanced cancer: potential benefits and challenges

Hannah R. Wardill,
Luke T. Wooley,
Olivia M. Bellas
et al.

Abstract: The side effects of cancer therapy continue to cause significant health and cost burden to the patient, their friends and family, and governments. A major barrier in the way in which these side effects are managed is the highly siloed mentality that results in a fragmented approach to symptom control. Increasingly, it is appreciated that many symptoms are manifestations of common underlying pathobiology, with changes in the gastrointestinal environment a key driver for many symptom sequelae. Breakdown of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“…A systematic review and meta-analysis revealed associations between cannabis usage and alterations in the human microbiome, which must be considered in future research on the therapeutic effects of cannabis on patients (May Soe et al, 2023). Cannabis extracts increased microbial diversity and richness in a mouse model of metabolic disease while promoting the enrichment of microbial taxa associated with health (Wardill et al, 2023).…”
Section: Personalized Medicine and Gut Microbiota Profilingmentioning
confidence: 98%
“…A systematic review and meta-analysis revealed associations between cannabis usage and alterations in the human microbiome, which must be considered in future research on the therapeutic effects of cannabis on patients (May Soe et al, 2023). Cannabis extracts increased microbial diversity and richness in a mouse model of metabolic disease while promoting the enrichment of microbial taxa associated with health (Wardill et al, 2023).…”
Section: Personalized Medicine and Gut Microbiota Profilingmentioning
confidence: 98%
“…A systematic review and meta-analysis revealed associations between cannabis usage and alterations in the human microbiome, which must be considered in future research on the therapeutic effects of cannabis on patients [104]. Cannabis extracts increased microbial diversity and richness in a mouse model of metabolic disease while promoting the enrichment of microbial taxa associated with health [105].…”
Section: Personalized Medicine and Gut Microbiota Profilingmentioning
confidence: 99%